2019
DOI: 10.1039/c9ta05179a
|View full text |Cite|
|
Sign up to set email alerts
|

Solvent-free vacuum growth of oriented HKUST-1 thin films

Abstract: H3BTC and Cu are sequentially deposited to form highly oriented HKUST-1 thin films under vacuum without the use of solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 115 publications
5
66
0
Order By: Relevance
“…18 Unlike in the solvothermal conversion of metal oxide layers to MOFs, 19 metal ions cannot be removed from the surface during MOF-CVD, leading to pinhole-free and conformal films. Vapor-phase growth of MOFs is a rapidly expanding area, 20 as illustrated by reports on the deposition of ZIF-67, 21 CuBDC, 22 CuCDC, 22 HKUST-1, 23 and a Zn-carboxylate-pyrazolate MOF-5 isotype structure. 24 Furthermore, related approaches have been developed such as CVD of amorphous precursors followed by postdeposition crystallization to form MOF-5, 25 IRMOF-8, 26 UiO-66 27 and UiO-66-NH2 28 , and the deposition of crystalline coordination compounds (e.g., CaBDC 29 , different CuBDC polymorphs 22,30 ).…”
Section: Introductionmentioning
confidence: 99%
“…18 Unlike in the solvothermal conversion of metal oxide layers to MOFs, 19 metal ions cannot be removed from the surface during MOF-CVD, leading to pinhole-free and conformal films. Vapor-phase growth of MOFs is a rapidly expanding area, 20 as illustrated by reports on the deposition of ZIF-67, 21 CuBDC, 22 CuCDC, 22 HKUST-1, 23 and a Zn-carboxylate-pyrazolate MOF-5 isotype structure. 24 Furthermore, related approaches have been developed such as CVD of amorphous precursors followed by postdeposition crystallization to form MOF-5, 25 IRMOF-8, 26 UiO-66 27 and UiO-66-NH2 28 , and the deposition of crystalline coordination compounds (e.g., CaBDC 29 , different CuBDC polymorphs 22,30 ).…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45][46] In this case, a precursor/seeds layer is firstly coated on the support, followed by steam/vapor-assisted conversion to form a continuous membrane layer. [42][43][44] Herein, as schematically shown in Figure S1 (Supporting Information), the a-Al 2 O 3 support is firstly coated with an oriented and thin ZIF-95 seeds layer by vacuum filtration of a suspension of ZIF-95 nanosheets. Then, in-plane epitaxial growth is done in mixed DMF/water vapor atmosphere to form an oriented and thin ZIF-95 membrane.…”
mentioning
confidence: 99%
“…[20] Adopting a LBL deposition technique, this PVD and CVD combined method was first developed for HKUST-1 thin films in our recent work as a bottom-up approach by sequential deposition cycles of metal atoms and ligand molecules. [20] As schematically described in Figure 6a, H 3 BTC (Benzene-1,3,5-tricarboxylic acid) molecules are known to form hydrogen bonded (H-bonded) 2D networks (typically one layer thickness) on a Cu (100) surface and also on various metal surfaces, such as Ag and Au. [51][52][53] Moreover, it was found that low coverages (~0.06 ML) of Fe on a Cu(100) surface can be coordinated with adsorbed H 3 BTC molecules forming 2D metalorganic network.…”
Section: Pvd and Cvd Combined Gas-phase Mof Thin Film Growthmentioning
confidence: 99%
“…We have recently made additional progress regarding bottom-up gas-phase MOF growth strategies adopting physical vapor deposition (PVD) of Cu and CVD of H 3 BTC in order to grow a HKUST-1 thin film under vacuum. [20] Developing gas-phase MOF thin film growth methods is important since such procedures can broaden the use of MOFs for various electronic and chemical applications. Thus, in this paper, we primarily investigate the current progress of gas-phase MOF thin film growth methods and also discuss future directions.…”
Section: Introductionmentioning
confidence: 99%